2021
DOI: 10.1002/jsfa.11653
|View full text |Cite
|
Sign up to set email alerts
|

Maternal oxidized soybean oil exposure in rats during lactation damages offspring kidneys via Nrf2/HO‐1 and NF‐κB signaling pathway

Abstract: BACKGROUND Cooking oil is an indispensable component of the human diet. However, oils usually undergo thermal oxidation. Oxidized soybean oil (OSO) has been shown to have detrimental effects on humans and has emerged as a root cause of many chronic diseases. The objective of this work was to evaluate the effects of puerpera exposure to OSO on kidney damage in the mother and offspring using lactating rats as an experimental model. RESULTS Pathological sections and ultrastructure showed that OSO exposure resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
3
7
0
Order By: Relevance
“…Studies have shown that LXR deletion not only interfered with the gestation adaptation of triglyceride metabolism in the liver but also caused abnormal fetal placental dyslipidemia due to the increased decomposition of maternal white fat . Meanwhile, in previous studies, we found that female rats supplementing oxidized oil containing high concentrations of lipid peroxidation products would affect the development and antioxidant status of fetuses and suckling pups. , In this experiment, F1 offspring showed the same trend as gestational F0 dams with increased oxidation degree. The mRNA levels of lipid synthesis-related genes LXRα, PPARγ, SREBP-1c, SCD-1, ACC, FAS, and CD36 were reduced.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Studies have shown that LXR deletion not only interfered with the gestation adaptation of triglyceride metabolism in the liver but also caused abnormal fetal placental dyslipidemia due to the increased decomposition of maternal white fat . Meanwhile, in previous studies, we found that female rats supplementing oxidized oil containing high concentrations of lipid peroxidation products would affect the development and antioxidant status of fetuses and suckling pups. , In this experiment, F1 offspring showed the same trend as gestational F0 dams with increased oxidation degree. The mRNA levels of lipid synthesis-related genes LXRα, PPARγ, SREBP-1c, SCD-1, ACC, FAS, and CD36 were reduced.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, our prior study found that exposure of rats to OSO during lactation will affect the kidney health of their offspring . It was also found in our study that a similar phenomenon occurred.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Fresh soybean oil (POV = 11.5 mEqO 2 kg −1 ) was bubbled with air at 65°C with a 4 L min −1 until the POV reached 220 mEqO 2 kg −1 . POV was determined by the previously described method (Gao et al, 2021). The POV was 11.5 mEqO 2 kg −1 for the fresh soybean oil group (FSO) and 220 mEqO 2 kg −1 for the oxidized soybean oil group (OSO).…”
Section: Methodsmentioning
confidence: 99%